2010
DOI: 10.1227/01.neu.0000386977.17441.98
|View full text |Cite
|
Sign up to set email alerts
|

Does Improving Medical Record Documentation Better Reflect Severity of Illness in Neurosurgical Patients?

Abstract: INTRODUCTION: While surgical resection has been shown to improve short-term local disease control, it remains debated whether surgical resection is associated with improved overall survival in patients with malignant primary osseous spinal neoplasms. We reviewed survival data from a US cancer registry spanning 30 years to determine if surgical resection was independently associated with overall survival.METHODS: The SEER registry was queried to identify cases of histologically confirmed primary spinal chordom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In fact, episodes with higher SOI levels usually present multiple co-morbidities affecting different organ systems (Averill et al, 2013). Thus, accurate and complete coding of co-morbidities is particularly important in APR-DRG classification as the patient’s SOI has a significant role in hospital payment (Spurgeon et al, 2011). For instance, in Portugal, a hospital that treats a patient assigned to APR-DRG 1944, which represents heart failure patients (base APR-DRG 194) with an extreme SOI, will be paid with an amount about five, three and two times higher than cases assigned to the same base APR-DRG with SOI levels 1, 2 and 3, respectively (Administração Central do Sistema de Saúde, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, episodes with higher SOI levels usually present multiple co-morbidities affecting different organ systems (Averill et al, 2013). Thus, accurate and complete coding of co-morbidities is particularly important in APR-DRG classification as the patient’s SOI has a significant role in hospital payment (Spurgeon et al, 2011). For instance, in Portugal, a hospital that treats a patient assigned to APR-DRG 1944, which represents heart failure patients (base APR-DRG 194) with an extreme SOI, will be paid with an amount about five, three and two times higher than cases assigned to the same base APR-DRG with SOI levels 1, 2 and 3, respectively (Administração Central do Sistema de Saúde, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their clinical significance, evidence elsewhere has shown that certain co-morbidities are generally under-reported in administrative databases (Austin et al, 2005), while the prevalence of others is overestimated when compared with the information of medical charts (Blumenthal, 1996; Chong et al, 2011; Hawker et al, 1997; Humphries et al, 2000; Iezzoni et al, 1992; Kieszak et al, 1999; Malenka et al, 1994; McCarthy et al, 2000; Mears et al, 2002; Newschaffer et al, 1997; Normand et al, 1995; Powell et al, 2001; Preen et al, 2004; Romano et al, 1994; Sarfati et al, 2010; Spurgeon et al, 2011; Waite et al, 1994). Overall, asymptomatic conditions tend to be under-reported in administrative datasets (Powell et al, 2001; Romano et al, 1994), while certain acute medical conditions or complications tend to be regarded by medical coders as more important than others, thereby originating this coding bias (Iezzoni et al, 1992).…”
Section: Introductionmentioning
confidence: 99%